Valiant NAVION stent graft system application: First Asian case‐series analysis. Issue 3 (1st February 2021) - Chow, Simon C. Y.; Ho, Jacky Y. K.; Fujikawa, Takuya; Lim, Kevin; Chu, Cheuk Man; Yu, Simon C. H.; Bashir, Mohamad; Wong, Randolph H. L.
Abstract: Background and Aim: The Valiant Navion TM stent graft system is a third‐generation low profile thoracic endograft designed for thoracic endovascular aortic repair. In this population analysis, we report on the first Asian all‐comers experience and outcomes who underwent thoracic endovascular aortic repair with the use of this new stent graft system. Methods: Between May 2019 and October 2020, 21 patients with different aortic pathologies were prospectively recruited and retrospectively analyzed. Important clinical and device‐related outcomes were evaluated. The endpoints included short‐term survival, technical success, access failures, major vascular and clinical complications, endoleaks, and hospital stay. Results: The commonest indication of stenting was penetrating aortic ulcers (28.6%) and six (28.6%) patients had emergency stenting performed for aortic transection or rupture. 30 days of survival postprocedure was recorded and complete. There were no major vascular complications. Deployment accuracy was 100%, and the technical success rate was 94.7% (18/19) with one patient having a Type 2 endoleak on follow‐up imaging. No neurological complications were noted. The mean operative time was 95 ± 73.6 min and the mean fluoroscopy time was 16.2 ± 10.8 min. Mean hospital stay for elective zone 2, 3, and 4 stenting was 5.3 ± 3.8 days, and only one patient postzone 1 thoracic endovascular aortic repair required a brief (0.5 days) ICU stay. All procedures were performed via the percutaneous transfemoral route with 100% success in percutaneous closure. Conclusion: This first reported Asian case series demonstrated versatility, safety, and efficacy of the Valiant Navion TM stent in Asian patients with different aortic pathologies.